Implementasi Geogebra Integrasi PowerPoint 365 terhadap Kemampuan Representasi Matematis pada Siswa Kelas XII - Rusli; Ilham Minggi; Latifa (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This study aims to determine the effect of the application of Geogebra integration PowerPoint 365 on mathematical representation ability in class XII. This research is pre-ecperiment with quantitative approach with techniques sampling is cluster random sampling. Data collection was carried using test result of mathematical representation ability (pretest and posttest), student quistionnaire responses, and observation sheets of student actvities. The data analysis technique used is descriptive and inferential statistical analysis. The result of descriptive statistical analysis showed: (1) the average pretest result were 47,78 (low category). The average posttest result were 88,89 (high category), (2) the posttest result show that classical completeness is achived 100%, (3) the average normalized gain is 0,8 (high category), (4) the average percentage of activity students by 90,5% (very active), (5) the average percentage of students quistionnaire responses by 92% (very good). The result of inferential statistic analysis show: (1) the average value of students tought using Geogebra integration PowerPoint 365 was greater than 70, (2) the normalized gain average value was greater than 0,3 (medium category), (3) the average classical completeness greater than 85%. In general it can be concluded that implementation Geogebra integration PowerPoint 365 has an effect on student mathematical representation ability.